A Conceptual Study Of Kala And Its Applied W.S.R To Diseases Occurring In Sharata Ritu - Baral, Saumyaleena; Sahoo, Manoj Kumar; Meher, Sushil Kumar; Panda, P K (International Research Journal of Ayurveda & Yoga, 2021)
Introduction- As per Ritu Kriyakala Pitta Prakopa occurs in Sharata Ritu, which results in Sharataritujanya Vikaras in human being. In order to pacify the aggravated Pitta, Samana therapy with Kakolyadigana drug in Hima form which is mentioned in Sushruta Samhita had been taken for study. Aim and Objective- To study the efficacy of Kakolyadi Gana Hima in various Pitta-Rakta janya diseases occuring in Sharata Ritu Materials and methods- 100 no. of patients were selected and kept on ‘Kakolyadigana drugs in Hima form’ 30 ml twice daily in empty stomach for a period of 10 days. All patients were investigated for DC, TLC, ESR, Hb gm% before and after treatment. The collected data was distributed according to different demography and Prakriti Pareeksha. The assessment of the subjective and objective parameters were evaluated by statistical w-test & paired t-test. Observation and results:-It had been observed that, the trial drug is statistically significant at level of 5% (p<0.5) to reduce both parameters. Discussion and Conclusion- Finally it can be said that the trial drug could be the best means for management of Pitta Vikara in Sharata ritu. During the entire duration of therapy, there was no found any adverse effect of drug reaction.